Identificación de la entomofauna en eltransecto n°3 parte b cantón Pujilí, provincia Cotopaxi, 2016 - Aispur Rivera, Oscar Fabricio (2016)
The present research aims to observe the effect of deforestation in the composition of entomofauna (micro fauna) of La Esperanza Parish of Pujilí Canton, where the investigative job was divided total area of the sector into transects, wich area is one hectare and is Located at coordinates Length: 73°5'4.781'' S, Latitude: 0°59'16.923'' W, at an altitude of 1970 m.a.s.l. The main objective of the project is know the diversity and abundance existing into the transect N° 3 in the pastureland zone, being predominant vegetation pasto miel (Paspalum dilatatum); The first step was the collection of samples through the use of “pit fall” traps, once all the necessary samples were obtained, the insects were identified and classified in the entomology laboratory by the use of dichotomous keys for their subsequent conservation.